Study on Mechanical Characteristics and Construction Control of the Railway Overlapping Tunnels - Fengjie, Yuan; Yang, Liu; Qianwei, Xu; Yuanlin, Zheng; Lisheng, Hu; Ping, Zhao; Yuebang, Cui (Frontiers in Earth Science, 2022)
In tunnel engineering, newly built tunnels will disturb the surrounding strata and close-to-existing tunnels, which may cause secondary lining cracking and overall damage to existing tunnels. In this paper, combined with the engineering problem of longitudinal cracks in the secondary lining of the lower tunnel caused by the super-close construction of a new tunnel in Chongqing, China, the deformation laws of the tunnel vault, inverted arch, and transverse brace during the construction of an overlapping tunnel are studied by using the finite element method. According to the distribution characteristics of stratum shear stress and plastic zone, the stratum and tunnel disturbance are analyzed. At the same time, combined with the field records, the causes and distribution laws of longitudinal cracks in the lower tunnel lining are explored. The research results show that the main reason for the cracking of the secondary lining is the bias effect of the post-excavation tunnel construction on the lower tunnel. When the tunnel spacing is small, the stratum maximum shear stress is concentrated, the penetration of the plastic deformation zone is more connected, and the settlement of the vault, horizontal convergence, and the deformation of the upper part of the arch waist of the lower tunnel are more intensified. This short-distance bias action causes the deformation of the stratum and the tunnel and eventually cracks in the lining.